Imeglimin prevents visceral hypersensitivity and colonic hyperpermeability in irritable bowel syndrome rat model - Tsukasa Nozu; Saori Miyagishi; Masatomo Ishioh; Kaoru Takakusaki; Toshikatsu Okumura (Elsevier, 2023)
Visceral hypersensitivity and leaky gut, which are mediated via corticotropin-releasing factor (CRF) and Toll-like receptor 4 are key pathophysiology of irritable bowel syndrome (IBS). Metformin was reported to improve these gastrointestinal (GI) changes. In this study, we attempted to determine the effects of imeglimin, which was synthesized from metformin on GI function in IBS rat models. Imeglimin blocked lipopolysaccharide- or CRF-induced visceral hypersensitivity and colonic hyperpermeability. These effects were prevented by compound C or naloxone. These results suggest that imeglimin may be effective for the treatment of IBS by improved visceral sensation and colonic barrier via AMPK and opioid receptor.